Framing the ‘demon’: a cognitive grammar analysis of the New York Times’ portrayal of Palestinians post-October 7, 2023 - Mohamad Jamil, Siti Nurnadilla (University of Rzeszów Press, 2025)
TABLE OF CONTENTS COMMITTEES 7 PREFACE 8 KEYNOTE SPEAKERS Raymond W. Gibbs, Jr. METAPHOR AND THE NATURAL WORLD 9 Christopher Hart CO-SPEECH GESTURES IN THE DISCURSIVE PERFORMANCE OF RIGHT-WING POPULISM 10 Jeannette Littlemore AMBIGUOUS METAPHORICITY AND EMOTIONAL EXPERIENCES: ALLOWING ROOM FOR FLEXIBILITY 12 Andreas Musolff COGNITIVE ANALYSIS OF CONSPIRACY THEORIES 13 SPEAKERS Shala Barczewska AMERICAN CULTURE WARS: METAPHORICAL CONSTRUALS OF SELF AND OTHER IN THE “WAR” AGAINST TEACHING EVOLUTION, CLIMATE CHANGE 16 Réka Benczes FROM CRIMINAL TO COMPANION: METAPHORICAL CONCEPTUALIZATIONS OF BREAST CANCER AMONG HUNGARIAN PATIENTS 18 Petra Bialkó-Marol TALKING ABOUT INFERTILITY: METAPHORS IN HUNGARIAN WOMEN’S NARRATIVES 20 Jacopo Castaldi AUTHORITY IN MULTIMODAL DISCOURSE: INSIGHTS FROM DOCUMENTARY FILMS 21 Laure Cataldo MILLIONS AND MILLIONS OF PEOPLE POURING IN: A MULTIMODAL ANALYSIS OF MIGRANTS’ REPRESENTATION AND THE ANTI-MIGRANT POSTURE IN TRUMP’S SPEECH 23 Monika Cichmińska “THE BASIS OF ALL LANGUAGE IS BODY LANGUAGE” – THE USE OF CONCEPTUAL METAPHORS IN ALEXANDER LOWEN’S BIOENERGETICS 25 Artur Czapiga PRAGMALINGUISTIC ANALYSIS OF INTERNET MEMES EXPRESSING DIRECTIVE SPEECH ACTS 26 3 Inga Dale THE ROLE OF VISUAL METONYMY OF HUMAN HANDS IN THE FRAMING OF KRZYSZTOF KIEŚLOWSKI’S “THREE COLOURS: WHITE” (1994) 27 Anna Dąbrowska FORGOTTEN MOVEMENTS. ON THE DISCURSIVE POTENTIAL OF DANCE AND THE ART OF COMMUNICATION 29 Jacek Fabiszak BAROQUE ‘CHOPP’D’ SYNTAX AND LINGUISTIC MANIPULATION IN SHAKESPEARE’S MACBETH 30 Małgorzata Fabiszak & Tomasz Michalik CULTURAL DIFFERENCES IN VISUAL ATTENTION: A PILOT EYE-TRACKING STUDY OF POLISH AND CHINESE MUSEUM VISITORS 32 Agnieszka Gicala METAPHORS IN THERAPY DISCOURSE: THEIR FUNCTION IN THE THERAPEUTIC PROCESS AND THEIR ROLE IN TRANSLATION 35 Elena Giribaldi THE BEAR RISES AND THE EAGLE SOARS: COMPETING METAPHOR SCENARIOS OF RUSSIA-US RELATIONS ON TWITTER/X 36 Joanna Jabłońska-Hood A COGNITIVE INTEGRATION ACCOUNT OF SOME CREATIVE BLENDS AND THEIR DETRIMENTAL USE BY MANOSPHERE MEMBERS ON FACEBOOK 38 Sinéad Jackson FALLING, SLIPPING, AND STUMBLING BACKWARDS: METAPHOR AND FRAMING IN UK-BASED ALCOHOL SUPPORT MATERIALS 40 Nur Sabrina Zafiran Mohd Jamil BEFRIENDING CANCER: METAPHORS OF CANCER IN MALAY WOMEN CANCER PATIENTS’ NARRATIVES 41 Siti Nurnadilla Mohamad Jamil FRAMING THE ‘DEMON’: A COGNITIVE GRAMMAR ANALYSIS OF THE NEW YORK TIMES’ PORTRAYAL OF PALESTINIANS POST-OCTOBER 7, 2023 43 Anna Jelec EIGHT PRINCIPLES FOR UNDERSTANDING PROFANITY 45 Ireneusz Kida QURANIC ALTERNATION OF DAY AND NIGHT: A METAPHOR SYMBOLIZING THE ABANDONMENT OF THE EARLIER BOOKS AND THE LAW 47 Robert Kiełtyka & Agnieszka Grząśko THE CONCEPTUAL METAPHOR POLISH NATIONAL IDENTITY DILEMMA IS HAMLET’S EXISTENTIAL DILEMMA PORTRAYED IN JACEK MALCZEWSKI’S HAMLET POLSKI (‘POLISH HAMLET’) 48 4 Beata Kopecka & Paulina Mormol-Fura IRONY IN MULTIMODAL CONSPIRACY-THEMED T-SHIRT DESIGNS 50 Krzysztof Kosecki ON THE NATURAL ENVIRONMENT IN TOK PISIN CONCEPTS 51 Hubert Kowalewski, Marta Szczecina-Nowosad CONCEPTUAL METAPHORS IN DEVICES OF INSTRUCTION DURING PILATES CLASSES 53 Marcin Kuczok ANIMAL DEATH METAPHORS IN ENGLISH AND POLISH ONLINE PET MEMORIALS: A CONTRASTIVE ANALYSIS FROM A COGNITIVE-SEMANTIC PERSPECTIVE 54 Marcin Kudła A MULTIMODAL ANALYSIS OF WWI SATIRICAL MAPS 56 Przemysław Łozowski “FINE FEATHERS MAKE FINE BIRDS”: IDENTITY IN-BETWEEN WORDS AND IMAGES 57 Aleksandra Majdzińska-Koczorowicz, Julia Ostanina-Olszewska INCLUSION THROUGH IMAGERY: EXPLORING VISUAL BLENDING IN DISCOURSE. THE “KNOW OR GET TO KNOW” SOCIAL CAMPAIGN 59 Beth Malory & Kathryn Allan “AS IF THE WOMB WERE HIRED BY MEN, AS MERCHANTS SHIPS ARE TO BE FRAITED BY THEM”: THE DISCURSIVE CONSTRUCTION OF PREGNANCY ACROSS THE HISTORY OF ENGLISH 60 Goran Milić PLEASE (DON’T?) STEP INTO MY CHAMBERS: ECHO CHAMBERS AND FIGURATIVE FRAFMING IN CROATIAN PRESIDENTIAL CAMPAIGN ONLINE DISCOURSE 62 Kundyz Mukhangali PARTNER, BROTHER, OR A FRIEND: CONCEPTUAL METAPHORS IN RUSSIA-KAZAKH RELATIONS 64 Alexandra Nagy-Béni & Réka Benczes WHERE DO OLDER WOMEN GO? VISUAL REPRESENTATION OF OLDER WOMEN IN HUNGARIAN ONLINE MEDIA DISCOURSE 65 Laura Narisano “AN EASY WORD TO SAY”: CONCEPTUALISATIONS OF SUSTAINABILITY IN MEDIA DISCOURSE 67 Olga O’Toole THE ROLE OF CODE-SWITCHING AND BORROWING IN THE POLISH MANOSPHERE: A CRITICAL DISCOURSE ANALYSIS OF INCELS IN THE POLISH ONLINE SPACE 69 5 Klaus-Uwe Panther, Linda L. Thornburg CULTURE AND COGNITION IN CLIMATE CHANGE CARTOONS 70 Kateryna Pilyarchuk ‘GIVE A GIRL THE RIGHT SHOES AND SHE CAN CONQUER THE WORLD’: WOMEN AS WARRIORS IN FASHION DISCOURSE 72 Agnieszka Poznańska LINGUISTIC STRATEGIES AND STEREOTYPE DECONSTRUCTION IN DAVID IVES’S POLISH JOKE 74 Anna Rogos-Hebda “A HORRID COMMUNITY”: THE DISCURSIVE CONSTRUCTION OF LEPROSY AND LEPERS IN HISTORICAL AMERICAN ENGLISH 75 Jaime Salvador-Grande VERBO-VISUAL IRONY AS A DISSOCIATIVE STRATEGY TOWARDS LEADERS INACTION IN CLIMATE CRISIS CARTOONS 77 Nina Shtok A CROSS-LINGUISTIC ANALYSIS OF NEWSWORTHINESS IN REPORTING ON TRUMP’S PRESIDENTIAL VICTORY IN RUSSIAN AND UKRAINIAN PRESS 79 Ida Stria “ENGLISH IS THE MOST UNSUITABLE LANGUAGE FOR INTERNATIONAL COMMUNICATION” – HOW ESPERANTO SPEAKERS BUILD THEIR IDENTITY ON PREJUDICE AND POWER STRUGGLES 80 Lilla Petronella Szabó & István Kollai BOUNCING BOUNDARIES: THE METONYMIC USE OF EAST AND WEST IN HUNGARIAN PRIME MINISTER VIKTOR ORBÁN’S POLITICAL SPEECHES 82 Vasia Tsami, Kyriakoula Tzortzatou, Nikoletta Panagaki LIQUID RACISM IN GREEK PARLIAMENT: ANALYZING CRITICALLY NARRATIVES ABOUT IMMIGRANT/REFUGEE ISSUES 84 Dóra Eszter Varga LIFE IS WAR? – CULTURAL METAPHORS AS PERSUASIVE DEVICES IN PÉTER MAGYAR’S POLITICAL COMMUNICATION 85 Anna Wyrwa LINGUISTIC VIEW OF TIME IN OLGA TOKARCZUK’S NOVEL PRAWIEK I INNE CZASY AND ITS ENGLISH TRANSLATION PRIMEVAL AND OTHER TIMES BY ANTONIA LLOYD-JONES 87 Monika Zasowska AUTHORIAL IDENTITY CONSTRUCTION IN LINGUISTICS AND PSYCHOLOGY BOOK REVIEWS 89 Edyta Źrałka ETHICAL ASPECTS OF SELF-CENSORSHIP IN CONTROVERSIAL ISSUES OF OKO.PRESS ARTICLES AND THEIR ENGLISH TRANSLATIONS